Analisis Elastisitas Substitusi Antara Tenaga Kerja Terampil dan tidak Terampil pada Industri Rotan di Desa Trangsan Kecamatan Gatak Kabupaten Sukoharjo - Sari Palupi, Dian, Dr. Agung Riyadi,M.Si (2017)
The purpose of this research is to analyze how the influence of skilled labor and unskilled labor to total production, and analyze how the elasticity of substitution between skilled labor and unskilled in the rattan industry in Trangsan village, Sukoharjo. The method of analysis using multiple linear regression model of the production function CES (Constant Elasticity of Substitution). This study uses primary and secondary data. Primary data were obtained by direct interviews and secondary data obtained from the village, the village cooperative Trangsan, and BPS Sukoharjo. Results from this study that skilled labor and unskilled labor a significant effect jointly to total production. There is a positive and significant impact on skilled labor to total production. There is positive and not significant in unskilled labor to total production in the rattan industry in the village Trangsan. The elasticity of substitution of 0.332 <1 (inelastic) shows the process of substitution of skilled labor by unskilled labor is relatively difficult to do.